Winter annual grassy weeds increase over‐winter mortality in autumn‐sown wheat. (1st February 2013) - Miller, Z J; Menalled, F D; Burrows, M; Lotz, Bert
Summary Over‐winter mortality, that is, winterkill, reduces cereal crop competitive ability and yield. While management and environmental variables are known to affect winterkill, the extent to which weeds contribute to increased winterkill is largely unknown. Winter annual weeds may increase winterkill through resource competition and by increasing incidence of and damage from plant pathogens that cause winterkill. We evaluated the impact of summer annual (Avena fatua) and winter annual (Bromus tectorum) weeds on the over‐winter survival rate of winter wheat over three winters, during which plots were covered with snow. Pink snow mould (Microdochium nivale), a winterkill pathogen known to infect B. tectorum and winter wheat, was common in wheat stands. In weed‐free treatments, mortality rates were initially near zero, but increased by nearly 45% in each subsequent winter, presumably due to an increase in snow mould disease in continuously cropped winter wheat. Whereas A. fatua infestation had no impact on crop survival rates, winter wheat survival in B. tectorum‐infested plots was 50% less than the weed‐free control in the second and third years of this study. Among B. tectorum‐infested plots, winter wheat over‐winter survival declined with increasing weed seed produced in the previous summer. Overall, this study demonstrated that winter annual weed infestations can reduce crop stand densities below replanting thresholds by reducing fall‐sown cereal winter survival. The effects of winter annual weeds on winter wheat may be meditated by increased proliferation of snow mould disease.